Laboratory Tests Required to Reach the Diagnosis in Patients with Grossly Elevated ESR - Haque, Md Zahirul; Alam, Saki Md Zakul; Noman, Mesbahuddin; Siddique, Md Abu Naser; Azhar, Md (Journal of Medicine, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This study was done in medicine indoor department of Rajshahi Medical College Hospital from January 2004 to March 2004. Consecutive 100 patients, who were found to have an ESR equal to or more than 100 mm in 1st hour, were included in this study. Among them 56 were male and 44 were female. All of them were classified in five age groups. Haematological disorder appeared to be the most common cause (41%) of marked ESR elevation; followed by infectious diseases (36%) and connective tissue disorders (17%). In 4% cases the cause can not be elicited. In this study, most commonly done investigation was peripheral blood film (76 patients) and gave positive clue to diagnosis in 45% cases. Bone marrow study was done in 53 cases and gave positive diagnosis in 69% cases. Other tests with high diagnostic yield were RA test (35%), X-ray spine (62%), Widal test (42%), Splenic aspirate study for kala-azar (46%), DAT for kala-azar (47%), FNAC of lymph node (77%), Pleural fluid study (100%). Most of the patients have needed 3 (46% patient) to 4 (27% patient) special investigations along with routine investigations to reach the diagnosis. doi:10.3329/jom.v10i1.1995 Â J Medicine 2009; 10: 7-11 Â Â